Transport studies through liquid membranes of ciprofloxacin and norfloxacin - Nagappa, A.N.; Kole, P.L.; Pandi, P.V.; Patil, R.T.; Zeeyauddin, K.; Shanmukha, I. (National Institute of Science Communication and Information Resources, CSIR, 2004)
Ciprofloxacin and norfloxacin, the widely used drugs have been shown to generate liquid membranes in series with a supporting membrane (Sartorius celluose acetate microfiltration membrane). Transport of dextrose and ions, such as NH4+, Mg2+ Ca2+, K+ and PO43- has been studied in the presence of liquid membranes generated by these drugs. The data obtained on the modification in the permeability of dextrose and ions in the presence of liquid membrane indicate the significance of liquid membranes in passive transport.